Macroscopic Mechanical Characterization of SMAs Fiber-Reinforced Hybrid Composite Under Uniaxial Loading - Lei, Hongshuai; Wang, Zhenqing; Tong, Liyong; Tang, Xiaojun (Journal of materials engineering and performance, 2013)
This paper presents an experimental and theoretical investigation on the macroscopic mechanical behavior of shape memory alloys (SMAs) fiber-reinforced glass/resin composite subject to uniaxial loading at ambient temperature. A series of unidirectional SMAs reinforced composite laminates is fabricated through vacuum-assisted resin injection. Scanning electron microscopy is conducted to evaluate the interfacial cohesive quality between SMAs fiber and matrix. A theoretical model is proposed based on the SMAs phase transformation model and rule of mixture. Uniaxial tensile tests are performed to study the effects of weak interface and SMAs fiber volume fraction on the effective modulus of composite. Failure morphology of composite is discussed based on the observation using digital HF microscope. Due to the effects of phase transformation and weak interface, the overall stiffness of SMAs composite at the second stage is on average 10% lower than theoretical results. The rupture elongation of experimental result is approximately 13% higher than theoretical result. The local interfacial debonding between SMAs fiber and glass/resin matrix is the main failure mode.